New Cryoprotectant Loading Method for Cell Droplet Vitrification with Continuous Evaporation - Cui, Mengdong (Langmuir : the ACS journal of surfaces and colloids, 2022)
Droplet-based vitrification is considered to be a promising cryopreservation method, which achieves high cell viability through high cooling rates and low concentrations of cryoprotective agents (CPAs). However, the droplet vitrification cryopreservation process needs in-depth research, such as the balance of the CPA concentration and the cooling rate, the CPA loading process, and the droplet encapsulation method. Here, we developed a chip with a high cooling rate for vitrification droplet encapsulation and provided a new method for continuous loading of low-concentration CPA droplets by evaporation. The results showed that the CPA droplet volume decreased exponentially with the evaporation time, and the larger the initial droplet size, the longer the evaporation time to achieve the critical vitrification concentration. There was no significant difference in the viability of MSCs, NHEK, and A549 cells between the evaporation loading vitrification method and the traditional slow freezing method, but the former was easier to operate and can balance the cooling rate and concentration by controlling the evaporation time. Moreover, a theoretical model was proposed to predict the CPA concentration inside the microdroplets dependent on the evaporation time. The current work provides a potential method to load low-concentration CPAs for cell vitrification preservation, which is more beneficial for cell therapy and other regenerative medicine applications